Anisotropic Parabolic Equations with Measure Data (Journal of Partial Differential Equations, 2001)
In this paper, we prove the existence of solutions to anisotropic parabolic equations with right hand side term in the bounded Radon measure M(Q) and the initial condition in M(Ω) or in L^m space (with m “small”).
Keywords: Anisotropic parabolic equations; measure data